2021
DOI: 10.3390/app112110291
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Hotel Room Occupancy Using Long Short-Term Memory Networks with Sentiment Analysis and Scores of Customer Online Reviews

Abstract: For hotel management, occupancy is a crucial indicator. Online reviews from customers have gradually become the main reference for customers to evaluate accommodation choices. Thus, this study employed online customer rating scores and review text provided by booking systems to forecast monthly hotel occupancy using long short-term memory networks (LSTMs). Online customer reviews of hotels in Taiwan in various languages were gathered, and Google’s natural language application programming interface was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…For workdays, they achieved 75.45% similarity on real (EDR) signals. Chang et al in [ 142 ] used six forecasting models to analyze the same dataset: Gaussian process regression, regression by least squares, regression by backpropagation, regression by general regression, and regression by LSTM. The numerical results demonstrated that LSTM networks were superior to the other models in estimating hotel accuracy rates across three data repositories.…”
Section: Data Analysis Approachmentioning
confidence: 99%
“…For workdays, they achieved 75.45% similarity on real (EDR) signals. Chang et al in [ 142 ] used six forecasting models to analyze the same dataset: Gaussian process regression, regression by least squares, regression by backpropagation, regression by general regression, and regression by LSTM. The numerical results demonstrated that LSTM networks were superior to the other models in estimating hotel accuracy rates across three data repositories.…”
Section: Data Analysis Approachmentioning
confidence: 99%
“…So far, few studies have investigated online reviews' usefulness for forecasting hotel demand. Wu et al (2022) and Chang et al (2021) are two typical studies that perform sentiment analysis on online reviews and utilize it in hotel demand forecasting. These two studies, however, consider only sentiment information from online reviews, which may result in a less accurate forecast.…”
Section: Related Workmentioning
confidence: 99%
“…(Al Shehhi & Karathanasopoulos, 2020) Modelo de pronóstico de series temporales Usa el espacio de estado estacional (Pereira, 2016) Modelo de serie temporal con fuente de datos big data Usa múltiples fuentes de big data (Pan & Yang, 2017) Modelo de redes neuronales Redes con revisión de puntaje (Chang et al, 2021) Tabla 1 -Métodos de previsión de datos en empresas turísticas Pese, a que se ha incrementado el número y tipo de técnicas numéricas en la hospitalidad, existe muy poca evidencia sobre el análisis de tarifas hoteleras. En este sentido Kim Modelo de tendencias para series complejas: caso de estudio tarifas hoteleras et al, (2020) desarrollaron un estudio de tarifas y la discrepancia entre los canales de distribución con la intención de conocer los criterios sobre los cuales se calculan los precios.…”
Section: Modelo De Precios De Las Habitacionesunclassified